German Anxiety Barometer—Clinical and Everyday-Life Anxieties in the General Population - Adolph, Dirk; Schneider, Silvia; Margraf, Jürgen (Frontiers in Psychology, 2016)
The objective of this study was to test a time-efficient screening instrument to assess clinically relevant and everyday-life (e.g., economic, political, personal) anxieties. Furthermore, factors influencing these anxieties, correlations between clinical and everyday anxieties and, for the first time, anxiety during different stages of life were assessed in a representative sample of the general population (N= 2229). Around 30% of the respondents manifested at least one disorder-specific key symptom within one year (women > men), 8% reported severe anxiety symptoms. Two thirds of respondents reported minor everyday anxieties and 5% were strongly impaired, whereby persons with severe clinical symptoms were more frequently affected. A variety of potential influencing factors could be identified. These include, in addition to socioeconomic status, gender, general health, risk-taking and leisure behaviour, also some up to now little investigated possible protective factors, such as everyday-life mental activity. The observed effects are rather small, which, however, given the heterogeneity of the general population seems plausible. Although the correlative design of the study does not allow direct causal conclusions, it can, however, serve as a starting point for experimental intervention studies in the future. Together with time series from repeated representative surveys, we expect these data to provide a better understanding of the processes that underlie everyday-life and clinical anxieties.